Stimulation of Pinus radiata seedling growth using ectomycorrhizal and saprophytic fungi as biofertilizers - Chávez, Daniel; Pereira, Guillermo; Machuca, Ángela (Bosque (Valdivia), 2017)
Free-living mycorrhizal-arbuscular and saprophytic fungi have been reported to be able to promote the growth of some plants. However, the combined use of ectomycorrhizal and saprophytic fungi as growth stimulators for forest species has not been much studied to date. To study the effectiveness of different biological inoculants prepared with the ectomycorrhizal fungi Suillus luteus and Rhizopogon luteolus and the saprophytic fungi Coriolopsis rigida and Trichoderma harzianum, in both isolated and combined form, as potential biofertilizers for the growth of Pinus radiata seedlings in greenhouse conditions, P. radiata plants were transplanted to individual containers with pine bark composted as substrate and inoculated with sporal inoculum of ectomycorrhizal fungi and solid mycelial inoculum of saprophytic fungi produced on wheat grains. When the assays were completed (10 months), the percentage of mycorrhization and some morphological parameters of the plants were measured to determine quality indices. The biological inoculants formulated with the saprophytic fungi or with the mixture of saprophytic and ectomycorrhizal fungi stimulated plant growth compared to the controls (plants without fungal inoculation). In addition, the presence of wheat grains in the inocula promoted the stimulating effect produced by the fungi on the growth of P. radiata. The inoculant formulated with the C. rigida-R. luteolus mixture produced P. radiata plants with higher quality indices under greenhouse conditions, and its use as a potential biofertilizer represents a viable alternative in the production of forest plant species.